Politics and prosthesis : representing disability in South Africa's Truth and Reconciliation Commission - Price, Neroli (Department of Historical Studies, 2016)
This dissertation aims to put two seemingly stable and unchanging categories, namely the 'nation' and the 'body', into conversation with each other in order to interrogate how the disabled body, in particular, became a site for nation building in South Africa's transition from apartheid to democracy in the 1990s. More specifically, this dissertation aims to explore how, framed by the Truth and Reconciliation Commission (TRC), different bodies took on disparate meanings that both affirmed and challenged the emergence of the euphemistically termed, 'New Nation'. Relying on insights from disability studies, postcolonial scholarship and critical race and gender studies, this dissertation endeavours to interrogate how the emergent post-apartheid state relied on the collective memory and identity generated through particular ideas of violence and politics evidenced by the injured bodies on display at the TRC. Drawing on the TRC transcripts, the TRC Final Report and the Truth Commission Special Report coverage of the proceedings, this dissertation seeks to ask new questions about the shifting and uneven sites of embodied meaning-making in post-apartheid South Africa.